Mitochondriotropic lanthanide nanorods: implications for multimodal imaging. Issue 57 (12th June 2020) - Singh, Harwinder; Sreedharan, Sreejesh; Oyarzabal, Esteban; Mahapatra, Tufan Singha; Green, Nicola; Shih, Yen-Yu Ian; Das, Manasmita; Thomas, Jim. A.; Pramanik, Sumit Kumar; Das, Amitava
Abstract : Two-photo active lanthanide nanorods as an efficient reagent for bimodal imaging. Abstract : Two-photon active mitochondriotropic lanthanide nanorods for high resolution fluorescence imaging. The presence of Gd in the nanorods also enabled us to utilize this material as a T1 –T2 dual-mode contrast reagent for recording magnetic resonance images of the mouse brain.